Triglyceride-Lowering Effects of a Modest Dose of Docosahexaenoic Acid Alone Versus in Combination with Low Dose Eicosapentaenoic Acid in Patients with Coronary Artery Disease and Elevated Triglycerides - Schwellenbach, Lisa J; Olson, Kari L; McConnell, Karen J; Stolcpart, Ryan S; Nash, James D; Merenich, John A (Journal of the American College of Nutrition, 2006)
BACKGROUND: Hypertriglyceridemia is a risk factor for coronary artery disease (CAD). The American Heart Association recommends 1000 mg of omega-3 fatty acids, docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), daily for cardioprotection and higher doses for triglyceride-lowering in patients with CAD. METHODS: This was a prospective, randomized, double-blind study comparing DHA to DHA + EPA in patients with CAD and triglycerides greater than 200 mg/dL. Subjects were randomized to either 1000 mg of DHA or 1252 mg of DHA + EPA for eight weeks. Baseline and eight-week laboratories were drawn to assess changes in the fasting lipid profile. The primary objective was to evaluate the change in triglycerides between the two groups at eight weeks. RESULTS: A total of 116 subjects were enrolled; 57 in the DHA group and 59 in the DHA + EPA group. Baseline characteristics were similar between groups. The mean age was 69.4 ± 9.1 years and 70.7% were male. Triglycerides decreased by an average of 21.8% in the DHA group (p < 0.001) and 18.3% in the DHA + EPA group (p < 0.001). The difference between groups was not significant. A greater proportion of subjects in the DHA group achieved triglyceride goal (less than 150 mg/dL) compared to the DHA + EPA group (24.6% versus 10.2%, p < 0.05). CONCLUSIONS: Our results indicate that the American Heart Association recommended cardioprotective dose of omega-3 fatty acids can also significantly lower triglycerides in patients with CAD. There do not appear to be significant differences in triglyceride-lowering between DHA only and DHA + EPA combination products when dosing is based on DHA.